(untitled) (Simbiótica. Revista Eletrônica, 2023)
From the perspective of the concept of necropolitics, created by Achille Mbembe, this article discusses the invisibilization of abject bodies in the pandemic context, which increased the condition of vulnerability and the annihilation of such bodies. Using a dialogue between the theoretical contribution of Achille Mbembe and Michel Foucault, taking biopower and biopolitics as devices of power and bringing them closer to decolonial thinking in the intersectionality between race, class, gender and sexuality. We work with the concept of biopower from the perspective of necropolitics and present how State policies act directly on LGBTQIA+ people, in order to determine who will live and who will die. Additionally, in order to denounce the ills caused to LGBTQIA+ people during the pandemic, we sought data provided by civil organizations, ANTRA and #VoteLGBT.